Respuesta :

9514 1404 393

Answer:

  a = √(b² +c² -2bc·cos(A))

  a = √(c² -b²)

Step-by-step explanation:

For sides a, b, c, and opposite angles A, B, C, the general form of the law of cosines is ...

  a² = b² + c² -2bc·cos(A)

An expression for 'a' can be written by taking the square root.

  a = √(b² +c² -2bc·cos(A))

__

If you recognize that cos(A) = b/c, then a substitution can be made:

  a = √(b² +c² -2(bc)(b/c)) = √(b² +c² -2b²)

  a = √(c² -b²) . . . . . . . same as the Pythagorean theorem

ACCESS MORE